Efeitos da bengala na marcha de indivíduos pós-acidente vascular encefálico: da revisão sistemática da literatura ao primeiro ensaio clínico aleatorizado - Patrick Roberto Avelino (2020)
The first study, a systematic review, investigated the effects of the cane after stroke. Searches were performed in seven databases. The outcome measures were walking speed, stride length, cadence and symmetry. The 12 included studies involved 239 participants. The results showed that the individuals walked 0.01 m/s slower with a single-point cane, and 0.06 m/s slower with a four-point cane, when compared to walking without a cane. In addition, walking speed with a single-point cane was 0.06 m/s higher, when compared to a four-point cane. The results for the other outcomes were inconclusive, due to the small number of studies. The second study aimed to translate and adapt the Modified Gait Eficcacy Scale (mGES) to Portuguese-Brazil, a scale that assesses the perception of walking confidence. The process followed standard guidelines, including translation, back-translation, synthesis of the translations, expert committee consultation, and testing of the pre-final version. Satisfactory results were found for the pre-final version test, since there was no problem in the writing and clarity of the items or in the scale objective. The final version of mGES-Brasil demonstrated satisfactory degrees of semantic, conceptual, and cultural equivalence in relation to the original version. For the reproducibility of mGES-Brazil, investigated in study 3, the scale was applied on two occasions, in 30 individuals after stroke. All individual items showed almost perfect levels of reliability (Kappa>0.80). The intraclass correlation coefficient was 0.99 and the Bland and Altman graph did not reveal any systematic errors. The standard error of measurement was 2 (3%), while the minimum detectable change was 6 (9%). Finally, study 4 refers to a randomized clinical trial that investigated the effects of the providion of a cane on walking and social participation of chronic stroke individuals. Fifty individuals were randomized into the experimental group, who received a single-point cane, and a control group, who performed stretching of the lower-limbs muscles. The primary outcome was walking speed (with and without a cane), while secondary outcomes were step length, cadence, walking ability, walking confidence, and social participation. Results were measured before the intervention, after intervention, one-month follow-up. There was no significant differences between the groups in walking speed without a cane in any of the primary and secondary outcomes. However, when using a cane, the experimental group walked 0.14 m/s faster than the control group after interventions and follow-up, suggesting learning effect. These findings provided evidence that using a cane for one month does not improve walking without the cane or social participation.